2020
DOI: 10.3171/2018.9.jns182022
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of secondary white matter injury in the visual pathway by pituitary adenomas: a multimodal study at 7-Tesla MRI

Abstract: OBJECTIVEThe objective of this study was to investigate microstructural damage caused by pituitary macroadenomas by performing probabilistic tractography of the optic tracts and radiations using 7-T diffusion-weighted MRI (DWI). These imaging findings were correlated with neuro-ophthalmological results to assess the utility of ultra–high-field MRI for objective evaluation of damage to the anterior and posterior visual pathways.METHODSProbabilistic tractography employing 7-T DWI was used to reconstruct the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
(55 reference statements)
3
10
0
Order By: Relevance
“…In addition, considering the reversibility of visual field defect after the surgery, edema or gliosis might be one of contributing factors. Our results were similar to a few previous studies that reported transsynaptic degeneration in sellar or parasellar lesions (1,17). Changes of DTI and NODDI parameters in the optic radiation may reflect transsynaptic degeneration, which has been reported as a mechanism of secondary pathology in the posterior visual pathways in conditions that primarily affect the anterior visual pathway, such as glaucoma (18,19) and optic neuritis (20,21).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, considering the reversibility of visual field defect after the surgery, edema or gliosis might be one of contributing factors. Our results were similar to a few previous studies that reported transsynaptic degeneration in sellar or parasellar lesions (1,17). Changes of DTI and NODDI parameters in the optic radiation may reflect transsynaptic degeneration, which has been reported as a mechanism of secondary pathology in the posterior visual pathways in conditions that primarily affect the anterior visual pathway, such as glaucoma (18,19) and optic neuritis (20,21).…”
Section: Discussionsupporting
confidence: 93%
“…Crush and stretch injuries to the optic nerve, tract and chiasm in animals reveal that demyelination is a primary process in the progression of delayed axonal degeneration ( 1 4 ). Human studies looking at compression of the optic chiasm have confirmed those findings and also suggested the possibility of rapid vision recovery ( 5 , 6 ). Unlike primary axotomy, in which axonal connections are immediately severed, delayed axonal degeneration is a potentially reversible process.…”
Section: Introductionmentioning
confidence: 75%
“…Crush and stretch injuries to the optic nerve, tract and chiasm in animals reveals that demyelination is a primary process in the progression of delayed axonal degeneration (1-4). Human studies looking at compression of the optic chiasm have confirmed these findings and also suggested the possibility of rapid vision recovery (5,6). Unlike primary axotomy, in which axonal connections are immediately severed, delayed axonal degeneration is a potentially reversible process.…”
Section: Introductionmentioning
confidence: 88%